Baseline cross-sectional imaging of locally advanced high-risk breast cancer facilitates highly customized radiation therapy in surgically inaccessible anatomical areas - Borowiec, Tomasz; Matkowski, Rafał; Cybulska-Stopa, Bożena; Kuniej, Tomasz; Kołodziejczyk, Andrzej; Dupla, Dorota; Maciejczyk, Adam (Frontiers in Oncology, 2025)
BackgroundRoutine medical imaging used for preliminary breast cancer workup, such as mammography (MMG) and ultrasound (US), has limited utility for radiation oncologists. We hypothesized that the inclusion of cross-sectional imaging (CT scan or PET-CT) prior to primary systemic therapy (PST) would improve clinical staging accuracy and facilitate customized postoperative radiation therapy planning. Therefore, this study aimed to compare the standard baseline imaging with extended radiological staging.MethodsTo assess our hypothesis, we performed a prospective, single-center study that included 132 participants who were recruited from October 2015 to March 2020. We quantified the value of cross-sectional imaging compared to those of MMG and US. Descriptive statistics, the Friedman and chi-square tests were performed, and p < 0.05 was considered significant.ResultsPatients were grouped into two cohorts: the CT scan cohort (n = 87) and the PET-CT cohort (n = 43). A comparison of the value of cross-sectional imaging with those of MMG and US revealed that staging and radiation planning were altered by this additional procedure. The originally determined disease stage changed in 36.8% and 51.2% of cases in the first and second groups, respectively. The consistency between the assessment of involved axillary lymph nodes using imaging (cN) and the postoperative pathology report (pN) were evaluated. In most cases, clinical and pathological evaluation were consistent, with χ2(1) = 18.98; p < 0.001 for CT scan, and χ2(1) = 6.41; p = 0.03 for PET-CT.ConclusionsCross-sectional imaging is recommended for patients with locally advanced high-risk breast cancer. A highly customized radiation therapy, including a dose boost, was administered in nine patients with affected lymph nodes that were surgically inaccessible. This procedure was facilitated by extended radiological staging.